Gendered AI in banking services: the influence of financial chatbots’ gender on consumer behaviour - Roozen, Irene; Raedts, Mariet; Claeys, Christel; Di Gennaro, Giulia (International journal of bank marketing, 2025)
PurposeThis study explores whether the gender of a financial chatbot influences how competent potential users perceive the chatbot to be and whether they would choose to use the chatbot themselves.Design/methodology/approachThe study had a between-subjects design: participants (N = 420, ages between 18 and 75) viewed and evaluated either a male or a female financial chatbot. Data were collected via an online questionnaire.FindingsMale chatbots led to a significantly higher willingness to consult the service and were perceived as more competent. Furthermore, AI-literacy and sensitivity to gender perspectives significantly influenced these findings.Practical implicationsThe findings offer actionable insights for financial institutions to optimise chatbot interactions by considering user preferences for male versus female chatbots, potentially guiding the development of more effective AI-driven financial services. Companies can use these insights to tailor chatbot gender strategies to meet user expectations better and enhance service satisfaction.Originality/valueThis study provides novel empirical evidence on the impact of chatbot gender in male-dominated financial services, revealing how AI literacy and gender sensitivity influence consumer behaviour and perceptions. Additionally, it contributes to the theoretical understanding of AI gendering and its societal implications.